Current Strategies for Tracheal Decellularization: A Systematic Review - Dhihintia Jiwangga; Ferdiansyah Mahyudin; Gondo Mastutik; null Juliana; Estya Nadya Meitavany (International Journal of Biomaterials)
The process of decellularization is crucial for producing a substitute for the absent tracheal segment, and the choice of agents and methods significantly influences the outcomes. This paper aims to systematically review the efficacy of diverse tracheal decellularization agents and methods using the PRISMA flowchart. Inclusion criteria encompassed experimental studies published between 2018 and 2023, written in English, and detailing outcomes related to histopathological anatomy, DNA quantification, ECM evaluation, and biomechanical characteristics. Exclusion criteria involved studies related to 3D printing, biomaterials, and partial decellularization. A comprehensive search on PubMed, NCBI, and ScienceDirect yielded 17 relevant literatures. The integration of various agents and methods has proven effective in the process of tracheal decellularization, highlighting the distinct advantages and drawbacks associated with each agent and method.